Impacts of sea level rise on economic growth in developing Asia. - Asuncion, Ruben Carlo (Metro Manila, Philippines Asian Development Bank, 2017)
This paper examines the impact of global sea level rise (SLR) on the economic growth, migration and tourism from various empirical studies and consolidates several sea level projections by 2100 under different scenarios. The paper also points out the regions or countries most vulnerable to SLR include atoll countries and small islands states like Kiribati and Singapore. In addition, it tackles several adaptation cost estimates for selected countries in developing Asia and summarizes adaptive strategies and mitigation as a response to SLR which include retreat, accommodation, and protection. Lastly, it presents policy recommendations for developing Asia to cope with increasing sea levels.
Keywords: Climatic change; Environmental economics; Electronic books